2020
DOI: 10.1021/acs.molpharmaceut.0c00071
|View full text |Cite
|
Sign up to set email alerts
|

Nanometer-Sized Aggregates Generated Using Short Solubility Controlling Peptide Tags Do Increase the In Vivo Immunogenicity of a Nonimmunogenic Protein

Abstract: Subvisible aggregates of proteins are suspected to cause adverse immune response, and a recent FDA guideline has recommended the monitoring of micrometer-sized aggregates (2–10 μm) though recognizing that the underlying mechanism behind aggregation and immunogenicity remains unclear. Here, we report a correlation between the immunogenicity and the size of nanometer-scaled aggregates of a small 6.5 kDa model protein, bovine pancreatic trypsin inhibitor (BPTI) variant. BPTI-19A, a monomeric and nonimmunogenic pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…Data analysis was performed using the continuous distribution c (s) analysis module in the SEDFIT program [28]. As a positive control, we used BPTI‐C5I, which was previously reported to produce subvisible oligomers [15,18].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Data analysis was performed using the continuous distribution c (s) analysis module in the SEDFIT program [28]. As a positive control, we used BPTI‐C5I, which was previously reported to produce subvisible oligomers [15,18].…”
Section: Methodsmentioning
confidence: 99%
“…In previous reports, we showed that short solubility controlling peptide tags (SCP‐tags) [11–13] attached at the C terminus of a host protein could be used to induce the formation of subvisible amorphous aggregates and thereby increase the immunogenicity of non‐immunogenic proteins [14,15]. In particular, a hydrophobic isoleucine tag attached to the C terminus of two model proteins, BPTI‐19A (58 residues; MW: 5.98 kDa) and DEN3ED3 (103 residues; MW 11.46 kDa), increased their immunogenicity by oligomerizing the proteins into small nanometer‐scale aggregates, and the immune response was long‐lasting with a T‐cell‐dependent activation of the B cells [16,17].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, after thorough washing with PBS-Tween, coloring was performed with 100µl/well of OPD substrate (0.4mg/mL in 50mM citrate buffer, pH4.5 supplemented with 4mM H 2 O 2 ) for 20 minutes followed by absorbance measurement at 450nm using a Multiskan Ascent (Thermofisher) microplate reader. Antibody titers were calculated from power fitting of absorbance versus reciprocal of serum dilution using a cutoff of 0.1 (OD 450nm ) above the background values [45].…”
Section: Methodsmentioning
confidence: 99%
“…The challenges associated with assembly and purification of multispecific antibodies may also result in an increased risk of immunogenicity. Moreover, critical quality attributes like aggregation, particle size, and polyspecificity are also thought to increase the likelihood of immunogenicity [ 88 , 89 , 239 , 242 , 243 , 244 ]. Given the unique immunogenic liabilities of multispecific antibodies and their increasing numbers in clinical trials, new tools for the analysis and reduction of immunogenic liabilities will be of increasing importance.…”
Section: Polyspecificty and In Vivo Propertiesmentioning
confidence: 99%